THE POLITICAL THOUGHT OF THE THINKER ISMAIL SABRY ABDULLAH - Zeyad Jihad Hamad (Scholar Express Journals, 2021)
This research attempts to shed light on some of the intellectual aspects of the thinker Ismail Sabri Abdullah, who is one of the most prominent contemporary Arab thinkers, and since it was difficult to understand all the propositions put forward by Abdullah, we focused on the two most important concepts in the thought of Ismail Sabri Abdullah, namely: Democracy and globalization. In light of this, the research was divided into two main topics. In the first topic, the concept of democracy in the thought of Ismail Sabri Abdullah was exposed, while the second topic dealt with the concept of globalization in the thought of Ismail Sabri Abdullah. Then the research ended with a conclusion that included the most important conclusions and then a list of sources
Keywords: Ismail Sabri Abdullah; Democracy and globalization; important